Raising the Dimensions and Variables for Searching as a Learning Process: A Systematic Mapping of the Literature - Machado, Marcelo de Oliveira Costa; Gimenez, Paulo Jose de Alcantara; Siqueira, Sean Wolfgand Matsui (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Search engines are great allies in our daily educational tasks. However, usually, these tools are prepared only for factual learning and are less effective when dealing with more complex learning tasks. Thus, in recent years, Searching as Learning (SAL) research area has been developing from proposals that target the main challenges involving learning during the search process. The effectiveness of educational technologies in providing appropriate instructions depends directly on the input information. Gathering information on what should be taken into account in a search as a learning process can support the development of specialized search engines to support learning. Therefore, we performed a systematic mapping of the literature in order to gather this information, raising the dimensions and their associated variables.